Culturally Competent Care for Native American and Alaska Native Childbearing Families. Issue 4 (July 2022) - Callister, Lynn Clark
Abstract : First Nations, Native American, Alaska Native childbearing women, or Aboriginal childbearing women and their families are vulnerable groups at risk for adverse maternal and infant outcomes, including higher rates of preterm birth and maternal and infant mortality. Our global health and nursing expert, Dr. Callister, provides an overview and suggestions for culturally competent care.